"I Don't Know Why I'm Crying": Understanding Emotional Experiences of Premenstrual Syndrome in Women - Rahmawati, Adelina; Arinda, Fiska Puspa (World Psychology, 2025)
Premenstrual Syndrome (PMS) impacts nearly half of women worldwide, with mood changes being a primary concern. However, research on young women's subjective experiences, especially in non-Western contexts, remains limited. This qualitative study examined how young adult women experience and cope with premenstrual mood fluctuations, investigating their management strategies and influencing factors. Using interpretative phenomenological analysis, six women aged 18-25 years with consistent premenstrual mood symptoms for minimum six months were interviewed. Data analysis revealed three key themes: women's experiences and perceptions of premenstrual mood changes, including identity struggles and contextual influences; diverse coping mechanisms including behavioral, cognitive, and social strategies; and the role of socioeconomic factors, education, and technology in PMS management. Participants employed various adaptive approaches, ranging from self-care routines and exercise to seeking social support and using digital resources. Results demonstrate that PMS experiences are complex and multifaceted, highlighting the importance of personalized, culturally appropriate methods for understanding and addressing premenstrual mood fluctuations in young women. These findings contribute to better comprehension of PMS management in early adulthood.